Effect of Cinnamon Powder Addition on Nutritional Composition, Physical Properties and Sensory Acceptability of Butter Biscuits - Ng, Sze Han; Wan Rosli, W. I. (2014)
Introduction: Demand for dietary fibre-enriched and low sugar bakery products is rapidly increasing due to the current high incidence of Type 2 diabetes mellitus. Cinnamon, a spice which acts as a natural sweetener and insulin mimetic is believed to have health benefits. The objective of this study was to determine the properties of butter biscuits containing cinnamon powder (CP) that partially replaced sucrose at levels of 0 (control), 2, 4 or 6%. Methods: Nutritional composition, physical properties and sensory acceptability of the biscuits were analysed using AOAC methods, texture profile analyser and 7-point hedonic scaling method, respectively. Results: Protein, ash and dietary fibre contents of the biscuits increased significantly (P < 0.05) whereas the moisture and sucrose contents were reduced significantly, proportionately to the increasing levels of CP. In texture profile analyses, increment of firmness and reduction of crispiness of the biscuits were detected with increasing levels of CP, but not significantly. The sensory scores for control and 2% CP biscuits were not significantly different for all the sensory attributes. Biscuits with 4% CP received lower scores only for aroma and appearance whereas the scores for colour, crispiness and flavour showed no significant differences compared to the control and 2% CP biscuit. Conclusion: The addition of 4% CP in biscuit could be an effective way to produce nutritious butter biscuits without any apparent change to its desirable physical properties and sensory acceptability.